Highly thermal-stable paramagnetism by rolling up MoS2 nanosheets. Issue 2 (12th December 2016) - Hwang, Da Young; Choi, Kyoung Hwan; Park, Jeong Eon; Suh, Dong Hack
Abstract : Using the combination of strain and phase engineering, we demonstrate that the 1T phase of MoS2 can be produced by rolling up MoS2 sheets (named as MoS2 nano-scrolls) through a gliding process for the S plane. Abstract : Controlling phase transitions through local strain engineering is an exciting avenue for tailoring the electronic and magnetic properties of materials at the nanoscale. Herein, we demonstrate a tunable semiconducting to metallic phase transition of two-dimensional transition metal dichalcogenides using strain engineering through rolled up MoS2 sheets (named as MoS2 scrolls). A phase incorporated structure for MoS2 nanoscrolls containing the maximum concentration of 1T phase (∼58%) with high thermal stability up to 473 K can be produced by a gliding–rolling process for the S plane. These phase transitions are irreversible by virtue of the van der Waals interaction between the layers of the nanoscrolls, which is relatively stronger than the bending strain. A high concentration of the 1T phase can tune the bandgap through temperature, and also the magnetic property from nonmagnetic to paramagnetic MoS2 . This study, which is able to control phase transitions by strain engineering in the field of 2D materials, proves an exciting avenue for tailoring the novel functional properties of low-dimensional materials.